The cost-effectiveness of exenatide once weekly compared with exenatide twice daily and insulin glargine for the treatment of patients with type two diabetes and body mass index ≥30 kg/m2 in Spain. (July 2013) - Fonseca, Tiago; Clegg, John; Caputo, Giuseppe; Norrbacka, Kirsi; Dilla, Tatiana; Alvarez, Maria
Abstract Objective: The objective of this analysis was to estimate the cost-effectiveness of exenatide once weekly (EQW) for the treatment of type two diabetes mellitus (T2DM) in Spain. EQW was compared against exenatide twice daily (EBID) and insulin glargine (IG). Methods: The IMS CORE Diabetes Model was used to project clinical and economic outcomes for patients with T2DM treated with EQW, EBID, and IG. Treatment effects and patient baseline characteristics were taken from the DURATION 3 and pooled DURATION 1 and 5 studies, in the comparison against IG and EBID, respectively. Unit costs and health state utility values were derived from published sources. To reflect diabetes progression, patients started on EQW or EBID, switching to insulin glargine after 3 years. The analysis was conducted from the perspective of the Spanish National Health Service over a time horizon of 35 years with costs and outcomes discounted at 3%. The base case included patients with a BMI > 30 kg/m2, which is in line with current prescription restrictions in Spain. Uncertainty was addressed through extensive one-way sensitivity analyses around key model parameters and a comprehensive probabilistic sensitivity analysis. Results: When compared with EBID, EQW was the dominant strategy, i.e., less costly and more effective. When compared to IG, the incremental cost-effectiveness ratio was estimated at €12, 084 per QALY gained. Sensitivity analysis indicated that the model projections were robust to the various scenarios tested. Limitations: Primary limitations of the analysis are common to other T2DM analyses and include the extrapolation of short-term clinical data to the 35 year time horizon and uncertainty around optimum treatment durations. Conclusion: The analyses indicate that EQW is a cost-effective option for the treatment of T2DM patients in Spain for patients with a BMI > 30 kg/m2 considering a willingness-to-pay threshold of €30, 000 per QALY gained.